The role of psychological safety in online tourism and hospitality learning (Journal of Applied Learning and Teaching, 2022)
This study proposes and tests a conceptual framework to examine how tourism and hospitality students’ psychological safety and personal resourcefulness in online learning reach their tourism and hospitality threshold learning outcomes. This research develops a conceptual framework integrating the conservation of resources and social information processing theories and the findings of a qualitative study through a sequential mixed-methods approach. Subsequently, the model is tested with online survey data using a structural equation modelling technique. The results suggest that, for psychological safety, students’ computer self-efficacy and peer collaboration significantly affect overall students’ perceived graduate outcomes, whereas lecturer support has no significant impact. Further analysis of the results, along with theoretical and practical implications, are likewise discussed.